SEPARATION OF NICKEL AND COBALT FROM RE-LEACH SOLUTIONS OF MIXED HYDROXIDE PRECIPITATE BY SELECTIVE OXIDATION USING OZONE AS AN OXIDANT - MAGNALITA OCTAVIANI (NIM : 12513032), ANGGIA
Hydrometallurgical process has an advantage for treating low-grade laterite ore because of its ability to recover cobalt as a by product. One of the methods that has been used to recover nickel and cobalt from pregnant leach solution is as an intermediate product such as Mixed Hydroxide Precipitate (MHP). Furthermore, refining of MHP can be done by ammonia or sulfuric acid re-leaching followed by solvent extraction. The separation of nickel and cobalt is a difficult task due to their similar chemical properties. The difference between these two elements is the stability of Co in the form of trivalent that can be easily precipitated. Strong oxidant is required to increase interface potensial of cobalt to its trivalent ions tability. Ozone is a strong oxidant with standard reduction potential 2.07 V. In the present study, dissolution behaviour of nickel and cobalt from MHP was studied and the efectiveness of ozone as an oxidant for separation of nickel and cobalt in releach solution of MHP was investigated. This study was divided into two stages, namely re-leach of MHP and oxidationprecipitation using ozone. Initial characterization of MHP was done by X-Ray Diffraction (XRD), X-Ray Fluorosence, Atomic Absorption Spectroscopy (AAS), and moisture analysis. Variations of acid concentration, temperature, and solid-liquid ratio were conducted to study the dissolution of nickel and cobalt. The effects of pH, precipitation time, injection rate of oxygen, and temperature were studied in oxidation-precipitation experiment. Characterization of oxidation-precipitation residue from the best condition were carried out by XRD analysis. The study of cobalt precipitation kinetics was carried out by applying an-n order homogenous chemical reaction kinetic models at temperature of 25oC, 50oC, and 60oC. The investigation results showed that the increased of acid concentration and temperature enhance the percentages of Ni and Co dissolution, while the increased of solid-liquid ratio decrease the percentages of Ni and Co dissolution. The best condition of re-leach experiment was achieved in a condition of acid concentration of 2 M, solid-liquid ratio of 100 g/L at temperature 95oC, in which the percentages of nickel and cobalt dissolution were 99,97% and 95,47% respectively. In oxidationprecipitation experiment, the increased of pH and precipitation time increase the percentages of cobalt precipitation. While, the increased of feed gas oxygen injection rate and temperature decrease the percentages of cobalt precipitation. The best condition of oxidation-precipitation was obtained at pH 5, feed gas injection rate of 1 lpm, precipitation time of 2 hours at room temperature, in which the percentages of cobalt precipitation was 99,94%. The kinetics of precipitation of cobalt followed zero order kinetics of chemical reaction with activation energy of -5.401 kJ/mol. The results of XRD analysis showed that CoOOH and MnO2 were formed from oxidationprecipitation of Co and Mn in re-leach solution of MHP using ozone.